KEKUATAN HUKUM DARI PERJANJIAN DI BAWAH TANGAN PERKARA KEPAILITAN - Alberta, Alberta; Gunadi, Ariawan (Jurnal Hukum Adigama, 2020)
Bankruptcy is a verdict issued by the Commercial Court, which results in general confiscation of all assets and wealth of a debtor. Whether it is owned now or in the future. The settlement would be done by a curator under the supervision of a supervisory judge. These officials were appointed immediately at the time the bankruptcy verdict is read. Substantiation at a bankruptcy case follows the regulation in the civil procedural law. Which regulates 5 evidence, that are written evidence (deed), witness, prejudices, and vow. This written evidence is divided by 2 forms, an authentic (notarial) deed and a private deed. Both have the same binding strength, however different when presented to the court as proof. Private deed is weaker, and it is an imperfect evidence since it had to be proven furthermore. Bankruptcy has to qualify the requirements stated in Article 2 and Article 8 of Bankruptcy Law 2004. With one of the terms is a simple substantiation. Which does not comply with the nature of a private deed. This shall be depended on the judge’s authority to decide.